Indonesia's Accession to the OECD: Strategic Motivation and Foreign Policy Challenges in the Era of Prabowo Subianto - Heriyana Heriyana; Istiq Agustina (International Journal Labs, 2025)
This study analyzes the strategic motivations and challenges of Indonesia's foreign policy in its membership process in the Organisation for Economic Co-operation and Development (OECD) during the administration of President Prabowo Subianto. Indonesia views OECD membership as a crucial step to accelerate the transformation of the national economy towards developed country status by 2045 through the implementation of transparent, inclusive, and sustainable global economic governance standards. Using a qualitative approach based on an integrative literature review, this study applies theories of foreign policy analysis and rational decision-making to understand the political, economic, and strategic considerations that shape Indonesia's decision. The findings indicate that the